2008
DOI: 10.1063/1.2838477
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the anomalous Hall effect in low Mn concentration (Ga,Mn)As

Abstract: We present magnetotransport in a series of Ga 1−x Mn x As ͑x ϳ 0.014͒ films. Both ordinary and anomalous Hall resistivities are analyzed in high magnetic field ͑up to 18.0 T͒ at various temperatures. The unique scaling behavior n ϳ 0.5 is found for the entire series, which is not compatible with existing scattering theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…As mentioned in Sec. I, the data presented by Shen et al 17 for lowconductivity (Ga,Mn)As follows a very similar scaling relation σ (AH) xy ∝ σ 1.5 xx (dashed-dotted line), which they claim to be incompatible with existing scattering theories. If the MR of a sample is large, the scaling relation in Eq.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…As mentioned in Sec. I, the data presented by Shen et al 17 for lowconductivity (Ga,Mn)As follows a very similar scaling relation σ (AH) xy ∝ σ 1.5 xx (dashed-dotted line), which they claim to be incompatible with existing scattering theories. If the MR of a sample is large, the scaling relation in Eq.…”
Section: Resultsmentioning
confidence: 58%
“…11,12,13,14,15,16 Whereas most papers concerning the AHE in (Ga,Mn)As are primarily focused on the metallic regime 11,12,13,14,15,16 , only a few systematic studies concentrate on the low-conductivity regime. 13,17,18 Allen et al 18 examined the AHE in digitally doped (Ga,Mn)As structures with hopping transport on the insulating side of the metal insulator transition (MIT). Recently, Shen et al 17 focused on the lowconductivity regime of (Ga,Mn)As with ρ xx between 0.01 and 2 Ω cm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples (both as-grown and annealed) described above were characterized by magneto-transport measurements using the six-probe Hall geometry with indium ohmic contacts in a Janis continuous helium flow cryostat equipped with a superconducting magnet system, allowing us to sweep the magnetic field up to 6 T at various temperatures between 2 and 300 K. The hole concentration in the samples was determined from magneto-transport data obtained at low temperature (< 10 K) using a method described in Ref. 20. The Curie temperatures of the samples were obtained from SQUID magnetization data.…”
Section: Sample Fabrication and Experimental Proceduresmentioning
confidence: 99%
“…9 and 19 applies to both intrinsic and side-jump mechanisms, making it difficult to distinguish between the two processes; and also given the fact that Mn atoms in these materials act simultaneously as the source of magnetic moments and as acceptors, which complicates the analysis of scattering processes in this material. Furthermore, several recent studies of (Ga,Mn)As samples have reported a universal empirical scaling relation between the anomalous Hall and the longitudinal conductivities σ xy ∝ σ γ xx with γ of about 1.6, which holds over a wide range of conductivities (between 0.01 and 100 Ω −1 cm −1 ) 13,14,20 . By very simple algebra (see Sec.…”
mentioning
confidence: 95%